Soviet repressions and resistance to them in Onuškis rural municipality (Trakai district) - Zizas, Rimantas (Genocidas ir rezistencija, 2025)
Due to the aggressive activities of the Soviet (red) partisans and the armed resistance of the village self–defenders, the so–called local self–defence, which had been established in south–eastern Lithuania since the autumn of 1943, the situation in the region had become exceptional already during the years of the German occupation. Where Soviet partisans and armed self–defenders were active, armed conflicts would break out between them, creating hotbeds of tension, hostility, and hatred, which affected people’s consciousness, influenced their motives for further action, and had lasting psychological implications, which later complicated relations with the reinstituted Soviet power.
Keywords: German occupation; Soviet partisans; Lithuanian resistance; repressions; terror